The Russian Revolutions of 1917: The Northern Impact and Beyond - Kulavig, Erik (Nordisk Østforum, 2021)
Erik Kulavig reviews The Russian Revolutions of 1917: The Northern Impact and Beyond edited by Kari Aga Myklebost, Jens Petter Nielsen and Andrei Rogatchevski.